ECHOCARDIOGRAPHIC CHARACTERISTICS OF RIGHT VENTRICULAR FUNCTION PARAMETERS IN HEART FAILURE PATIENTS AT THE DEPARTMENT OF CARDIOLOGY, BAI CHAY HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the echocardiographic characteristics of right ventricular functional parameters in heart failure patients at the Department of Cardiology, Bai Chay Hospital.Subjects and Methods: A cross-sectional study was conducted on 60 heart failure patients treated at the Department of Cardiology, Bai Chay Hospital, from March 2025 to August 2025. Diagnosis was based on the 2023 ESC (European Society of Cardiology) criteria. Echocardiography was performed using Philips ultrasound systems.Results: The mean age of the participants was 73.4 ± 10.6 years (range: 52 to 94). There was a male predominance with a ratio of approximately 2:1. The prevalence of right ventricular (RV) systolic dysfunction was 65% based on TAPSE, 51.7% based on FAC (FAC < 35%), and 60% based on S' (S' < 9.5 cm/s). The rate of RV dysfunction according to the RIMP index (RIMP > 0.54) was 23.3%. RV diastolic dysfunction was 28.3% based on E/e' (E/e' > 6) and 26.7% based on E/A ratio. The proportion of patients with both systolic and diastolic RV dysfunction was 45%.Conclusion: Heart failure patients exhibit a high prevalence of both systolic and diastolic right ventricular dysfunction, primarily characterized by reductions in TAPSE, S’, and FAC.
Keywords: right ventricular function, heart failure, echocardiography.